Disaster management in the context of health security - DUMITRAS, Vasile (One Health & Risk Management, 2022)
Disasters are natural, man-made and social events with particularly serious consequences for the environment, as well as the health of people and animals. This category includes: earthquakes, catastrophic floods, volcanic eruptions, chemical, biological, nuclear accidents, damage to hydrotechnical constructions or main pipelines, mass fires and explosions, major accidents on communication routes, military conflicts, wars, epidemics, pandemics, etc.